2016
DOI: 10.1377/hlthaff.2015.1457
|View full text |Cite
|
Sign up to set email alerts
|

Affordable Care Act’s Mandate Eliminating Contraceptive Cost Sharing Influenced Choices Of Women With Employer Coverage

Abstract: Patient cost sharing for contraceptive prescriptions was eliminated for certain insurance plans as part of the Affordable Care Act. We examined the impact of this change on women's patterns of choosing prescription contraceptive methods. Using claims data for a sample of midwestern women ages 18-46 with employer-sponsored coverage, we examined the contraceptive choices made by women in employer groups whose coverage complied with the mandate, compared to the choices of women in groups whose coverage did not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 14 publications
3
50
2
Order By: Relevance
“…They perform their analysis on a smaller population of women in the upper Midwest, but they also have several additional months of data. The consistency of my results with the results from Carlin, Fertig, and Dowd () suggests that the short‐term effects of the ACA mandate remained stable across insurers and geographic regions.…”
Section: Discussionsupporting
confidence: 77%
“…They perform their analysis on a smaller population of women in the upper Midwest, but they also have several additional months of data. The consistency of my results with the results from Carlin, Fertig, and Dowd () suggests that the short‐term effects of the ACA mandate remained stable across insurers and geographic regions.…”
Section: Discussionsupporting
confidence: 77%
“…Between 2012 and 2014, the percent of privately insured women who paid $0 out-of-pocket for contraception increased by 30-50 percentage points across methods (Bearak, Finer, Jerman, & Kavanaugh, 2016;Sonfield, Tapales, Jones, & Finer, 2015). 15 An analysis of 499 Midwest firms that provide health insurance found this policy caused a 2.3 percentage point (7.6%) increase in prescription contraception use (Carlin, Fertig, & Dowd, 2016). A few hundred dollars can be meaningful to lower income women, but the reduction in cost was much higher for many women.…”
Section: Policy Backgroundmentioning
confidence: 99%
“…The fearful and emotional nature of women’s worries about cost stand in stark contrast to expressions of disbelief by politicians that women have trouble affording contraception [9]. Indeed, studies have shown that cost is a significant barrier to consistent use of effective contraceptive methods [1012]. Conversely, when cost barriers are removed, women are more likely to use prescription methods and to select highly effective methods such as IUDs and implants [10, 13], which have considerable upfront costs if paid out-of-pocket.…”
Section: Discussionmentioning
confidence: 99%